Development of near real-time monitoring and data archival of UiTM-SID system / N.A. Zakaria …[et al.] - Zakaria, N.A.; Aziz, A.; Wan Mokhtar, W. Z. A.; Jusoh, M. H. (Universiti Teknologi MARA, 2019)
The Stanford Solar Center has reputable partnership with almost 80 countries to form the Space Weather Sudden Ionospheric Disturbance (SID) Monitor Program. SID is a condition of sudden high ionization occurred at the lower ionospheric D-region caused by solar activity namely solar flare. UiTM-SID monitoring system located at Universiti Pendidikan Sultan Idris, UPSI (3.71’, 101.53’), is developed to monitor diurnal variation of the lower ionosphere layer and the activity of Solar flare by using Very Low Frequency (VLF) probing technique. Due to several issues with manual collection of data archival purposes, this paper presents near real time data monitoring at established university’s website and data archival for the purpose of data monitoring and data backup. The Design and implementation of UiTM-SID system have been done by using MATLAB software. The data was received using File Transfer Protocol (FTP) access and the data is stored in Google Drive cloud storage. The UiTM-SID is enhanced to have a near real-time monitoring system at the official website https://fke.uitm.edu.my/see-uitm/. At the website, it will display two signals strength data from VLF transmitter stations South Vijayanarayanam, India and North West Cape, Australia with frequency 19.2 kHz and 19.8 kHz respectively.